The role of phraseological units in the study of the Russian language in the framework of the updated school program (Eurasian Journal of Philology Science and Education, 2022)
The article discusses phraseological units within the framework of the updated school curriculum of the Republic of Kazakhstan. What is phraseology and how do students understand this term? The modern speech of the younger generation is characterized by an insufficient lexical stock, it often completely lacks phraseological units. The use of phraseological units helps to express the speaker’s thoughts most accurately. In everyday communication, when faced with phraseological units, many children do not always correctly interpret their meaning and meaning. This is becoming an increasingly urgent problem today. There is still no precise definition of the terms “phraseology” and “phraseologism” among researchers, and there is also no consensus on the correct use of the term indicating a unit of phraseology. The phraseological unit has such properties as idiomaticity, stability, therefore, as such, it is easily deduced from the public and literary-artistic thesaurus and reproduced in essentially different communicative functions. Phraseology is one of the areas of linguistics that represents stable expressions. The terminological description of phraseological units is comprehensively reasoned, the use of the term phraseological unit is justified, characteristic features are classified. The authors conducted a survey among school students, prepared an analysis of the results of this survey on the need to study phraseological units in the school curriculum. Determining the place and nature of phraseological units in the updated school curriculum, the basics of mastering this topic by students in accordance with their age are discussed. The survey showed that the majority of schoolchildren understand the meaning of phraseological units, are able to apply them in speech, however, as mentioned above, there are problems of their incorrect interpretation. Middle-level schoolchildren cannot always explain the meaning of phraseological units